CLOUD-RADIATIVE FORCING OVER THE SNOW-COVERED SURFACE AROUND ASUKA STATION, ANTARCTICA - アオキ, テルオ; ヤマノウチ, タカシ; AOKI, Teruo; YAMANOUCHI, Takashi (National Institute of Polar Research, 1992)
P(論文) Cloud-radiative forcing at the snow-covered surface in Antarctica was estimated from data of the radiation budget observation at Asuka Station (71°31'S, 24°08'E, 930m) in 1988. Cloud-radiative forcing at the top of the atmosphere was also estimated from satellite data in December 1988. It was found that shortwave forcing was negative (cooling) at the surface and positive (heating) at the top of the atmosphere. The longwave forcing was positive both at the surface and at the top of the atmosphere. The (shortwave+longwave) forcing was positive both at the surface and at the top of the atmosphere. This is different from those in middle and the low latitudes. The cloud-radiative forcing distributions at the top of the atmosphere in the extended region from the sea to inland were estimated from the satellite data in December 1988. The results indicated that the shortwave forcing was positive over the snow-covered region except the high inland, and negative over the sea. The longwave forcing was positive over all regions. The (shortwave+longwave) forcing was positive over the snow-covered regions except the high inland plateau, and negative over the sea. departmental bulletin paper